2021
DOI: 10.3390/microbiolres12010012
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Community Diversity and Composition as Affected by Tillage Intensity Treatments in Corn-Soybean Production Systems

Abstract: Our understanding on the effects of tillage intensity on the soil microbial community structure and composition in crop production systems are limited. This study evaluated the soil microbial community composition and diversity under different tillage management systems in an effort to identify management practices that effectively support sustainable agriculture. We report results from a three-year study to determine the effects on changes in soil microbial diversity and composition from four tillage intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Meanwhile, SOC, a vital source in the microbially driven carbon cycle, was mainly distributed in the topsoil, and therefore, the changes in pH and SOC are more associated with the soil bacteria ( Puissant et al, 2015 ; Cao et al, 2016 ). The studies have identified the soil pH and tillage as important factors determining the distribution pattern of microorganisms ( Xia et al, 2020 ; Shanmugam et al, 2021 ). The soil pH was an important factor that influenced the structure and diversity of soil metabolism and bacterial community ( Siles and Margesin, 2016 ; Cheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, SOC, a vital source in the microbially driven carbon cycle, was mainly distributed in the topsoil, and therefore, the changes in pH and SOC are more associated with the soil bacteria ( Puissant et al, 2015 ; Cao et al, 2016 ). The studies have identified the soil pH and tillage as important factors determining the distribution pattern of microorganisms ( Xia et al, 2020 ; Shanmugam et al, 2021 ). The soil pH was an important factor that influenced the structure and diversity of soil metabolism and bacterial community ( Siles and Margesin, 2016 ; Cheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bacterial community composition of the bottom soil also changed. On the contrary, tillage might have reduced the habitat heterogeneity, favoring few bacteria and helping them outgrow other competitors; this eventually changed the bacterial community ( Shanmugam et al, 2021 ), by altering the chemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are indications that an increase of these genera is more directly linked to tillage. Actinobacteria and specifically members of the genus Streptomyces were found to be increased in abundance under reduced tillage regimes, which was likely due to increased residues of organic material on the soil surface (Shanmugam et al, 2021;Zaitlin et al, 2004). Also, Lysobacter has been found to be increased in abundance under non-inversion tillage and was positively correlated to the C/N ratio (Sun et al, 2020).…”
Section: Effect Of Tillage On Soil Biological Propertiesmentioning
confidence: 93%
“…In line with this, a study found that after two years, the remaining biomass of 14C-labelled wheat residue was significantly lower under conventional tillage (25.8%) compared to reduced tillage (40.0%), corroborating the hypothesis that conventional tillage accelerates residue decomposition [ 68 ]. However, it is important to note a general trend of diminished bacterial diversity associated with conventional tillage [ 69 , 70 , 71 ]. Interestingly, Duan and colleagues [ 72 ] suggest that the increase in alpha diversity observed under conventional tillage might result from the disturbance of soil aggregate stability and the subsequent release of physically protected organic matter, which is then utilized by microbes.…”
Section: Agricultural Practices Enhance the Development Of Microbial ...mentioning
confidence: 99%